Network as a service for next generation internet - Duan, Qiang, 1970-; Wang, Shangguang (IET telecommunications series ;, 2017)
This book presents the state of the art of the Network-as-a-Service (NaaS) paradigm, including its concepts, architecture, key technologies, applications, and development directions for future network service provisioning. It provides a comprehensive reference that reflects the most current technical developments related to NaaS.